Analisis Pengaruh Likuiditas, Solvabilitas dan Aktivitas terhadap Profitabilitas pada Perusahaan Manufaktur Makanan yang Terdapat di Bei Periode 2017-2020 - Herlina Novita; Rokky Lumban Gaol; Ramahmo Matanari; Monalisa Siahaan; Delkawati Sarumaha (Owner : Riset dan Jurnal Akuntansi, 2022)
This research was conducted on food and beverage company that listed in Bursa Efek Indonesia,i This research aims to examine and analyze the effect of Current Rasio, Debt to Asset, Debt to Equity, Total Aset Turn  Over on return of Asset. The Approach that taken in this research is quantitative and descriptive approach, population in this research are 30 companies with using purposive sampling technique and the sample amounted to 24 companies, so the total number of observations was 96 observations. However, due to the data being too extreme, somedata had to be removed in this observation by recovering 18 data’s so the total of observations used in every test are 78 data. The analytical Method that use in this research is multiple value regression method. From the result of this research simultaneously Current Rasio (CR), Debt to Asst (DAR), Debt to Equity (DER) and total Asset Turn Over (TATO) have a positive effect on Return on Assets (ROA) listed on the BEI period 2017-2020, with the result of F-hitung > F-table (2,697>2,50) with a significance value of 0,037 < 0,05. And from the partial test result that CR, DAR, DER, TATO have a no significant negative effect on ROA.